ANALISIS KESIAPAN PROGRAM STUDI DALAM PRODUCTION BASED EDUCATION: STUDI PADA PROGRAM STUDI D3 AKUNTANSI POLINES - Ardiansah, Muhammad Noor (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
There has been no clear studies to identify, verify and analyze readiness program resources in order to study the implementation of PBE resulted in initial position (existing point) is not clear that the priority programs and activities that are carried out per year tend to be responsive and not directed priorities. These conditions resulted in analysis of resource readiness courses in the management of production-based learning pattern PBE draw conducted This study aims to identify and verify and analyze readiness resources management courses in the pattern of production based learning, particularly in the Accounting Studies Program. This research is expected to be used to increase the effectiveness of learning and vocational education to improve the quality and relevance of polytechnic graduates. Total score was 33 the existence of resources from the scale of 12-60. The average score is 2.75. The average score was shown the position of Prodi's resources have been used, but its role is unclear (repeatable) tend to have clearly defined functions, communicated and documented (defined). Resources have been managed, monitored and evaluated well (managed) are: curriculum resources, networking courses, lab facilities, ISO-based management. Resources have been used but not optimal role: resources module practice, the formulation of an internship, practice material / TA, the performance of IC-based lecturer